Exploration on the Stratification of the Ground Substrate Survey and the Design and Construction of Its Testing Indicator System - Jiufen LIU; Xiaofeng ZHAO; Hongxing HOU; Tian QIN; Zhansheng CHEN; Liming XU; Ke YANG; Fanpeng KONG; Xiaohuang LIU; Bing LU; Ziqi LI; Jia LIU; et al. (Yankuang ceshi)
The ground substrate layer is the main carrier of the material and energy cycle of the earth’s surface. At present, it is essential to have a suitable ground substrate stratification and testing index system for conducting an effective ground substrate survey. Based on the pilot results of the ground substrate survey project in the past three years, and the links between ground substrate with Multi-Objective Regional Geochemical Surveys, the Third National Soil Census and the National Detailed Survey of Soil Pollution on Agricultural Land, the ground substrate can be vertically divided into three layers: the surface production layer (0-2m), the middle ecological layer (2-10m) and the deep sedimentary layer (10-20m). If the depth of the base layer is less than 20m, the ground substrate is exposed to the bedrock. The surface layer mainly serves the national food security, and mainly collects data; the middle layer focuses on territorial space planning, and is the focus of investigation; the deep layer is mainly to explore the ground substrate from bedrock-deep layer-middle layer-surface layer succession pattern, a small amount of engineering control is appropriate. The proposed vertical stratified test index system for ground substrate includes 4 required indices and N selected indices. The established stratification and stratification test index system of ground substrate can provide reference for standardizing the ground substrate survey and promote the high-quality development of the ground substrate survey. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202310080157.